Paciente de sexo femenino de 50 años de edad con hepatitis aguda alcohólica - Valle Vera, María José (2021)
The present clinical case is about a 50-year-old female patient who visits a doctor for jaundice, weight gain, fatigue, generalized weakness, decreased appetite, nausea and mild abdominal pain, is diagnosed with acute alcoholic hepatitis, which is carried out in the care process in order to improve their nutritional status. In the nutritional care process, the patient was evaluated using anthropometric, biochemical, clinical and dietary indicators reflecting a nutritional diagnosis of excessive alcohol intake (NI-4.3) related to his considerably increased habit of alcohol intake 3 months ago, evidenced by presenting jaundice , weight gain, fatigue, generalized weakness, decreased appetite, nausea and mild abdominal pain, also presents weight gain due to inadequate eating habits that is considered for nutritional treatment. A dietary plan was implemented according to the pathology, nutritional status and nutritional requirements as part of the medical treatment, as well as recommendations such as abstinence from alcohol and vitamin supplementation to correct micronutrient deficiencies. A control was established for the monitoring of the dietary plan and the patient, where beneficial responses are observed in the indicators of the nutritional evaluation, obtaining a decrease in weight, laboratory data, and a decrease in signs and symptoms due to acute alcoholic hepatitis.